(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
The microbial community that makes up the human microbiome has a significant impact on the immune system, central nervous system, and gastrointestinal tract. These microbes, which are derived from both maternal and external sources, are mostly found in the GIT and are important for metabolism and development. Drug usage, lifestyle, environment, and host genetics all affect the makeup of the gut microbiota. An imbalance in gut microorganisms known as dysbiosis is increasingly associated with neurological conditions, highlighting new treatment opportunities. Novel investigations regarding the function of gut microbiome in disorders like epilepsy, Parkinson’s, schizophrenia, Alzheimer’s, autism, and stroke are promising. Recent research highlights the critical role of gut microbiota in the two-way communication between the gut and the brain, which influences behaviour, neural development, and the development of neurological disorders. Although research on animals has improved our knowledge, clinical data points to the its possible involvement as a risk factor for neurological conditions. Extensive study investigates the potential impact of gut microbiome beyond gastroenterological diseases, including psychiatric disorders. This review explores the many routes involved in the communication between the nervous system and the gut bacteria, shedding light on the complex relationships between these two systems. It looks at changes in the microbiome and how they relate to neurological diseases and psychiatric illnesses.